2003
DOI: 10.1002/chin.200340236
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Transportation Fuels with Zeolites under Ambient Conditions.

Abstract: Fuel technology Fuel technology V 0400Desulfurization of Transportation Fuels with Zeolites under Ambient Conditions.-Cu + and Ag + zeolite Y, prepared by ion exchange of NaY zeolite with Ag + or Cu 2+ , adsorb sulfur compounds from commercial fuels (gasoline, diesel, and jet fuels) selectively and with high sulfur capacities at ambient temperature and pressure. The sulfur content in a commercial diesel is reduced from 430 to <0.2 ppm (by weight) at a sorbent capacity of 34 cm 3 of clean diesel produced per gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
178
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(179 citation statements)
references
References 1 publication
0
178
1
Order By: Relevance
“…3). Cation-bonding between electron-rich aromatic structures and metal ions and ammonium ions toward molecular recognition and selective metal binding had been well documented in the literatures [15,31]. For example, Qu et al found that the presence of tetra-alkyl ammonium largely enhanced the sorption NAPH, PHEN and PYR on smectite mainly due to formation of strong cation-EDA complexes between ammonium cation and PAHs [15].…”
Section: Effect Of Different Species Ofmentioning
confidence: 98%
“…3). Cation-bonding between electron-rich aromatic structures and metal ions and ammonium ions toward molecular recognition and selective metal binding had been well documented in the literatures [15,31]. For example, Qu et al found that the presence of tetra-alkyl ammonium largely enhanced the sorption NAPH, PHEN and PYR on smectite mainly due to formation of strong cation-EDA complexes between ammonium cation and PAHs [15].…”
Section: Effect Of Different Species Ofmentioning
confidence: 98%
“…Scientific efforts focus on oxidation [1,2], photoxidation [3,4] or adsorption . The adsorption based methods applied activated alumina [7,8], zeolites [9], and activated carbons [7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] as adsorbents. The results obtained on the latter materials seem promising [12,22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, both C300 and A100 MOFs were considered for further studies. From the quantities of S retained at equilibrium it results that the extent of DBT adsorption on MOF systems investigated in the present work is in the order of 6-8 times higher than that previously reported using conventional Y zeolite or activated carbons sorbents (Yang et al, 2003;Zhou et al, 2006). Due to the excellent performance of the MOF systems several parameters influencing their adsorption capacity were examined.…”
Section: Adsorption Of Dbt On Mofsmentioning
confidence: 66%
“…Y-zeolite has been selected because it is a microporous, crystalline material with a high adsorption capability often employed in the removal of sulfur compounds from liquid fuels (Hernandez-Maldonado and Yang, 2004;Yang et al, 2003). One important characteristic of these isotherms is that the extent of adsorption of the three organo-sulfur compounds at any concentration in liquid-phase is much lower than that reached on the C300 MOF system.…”
Section: Adsorption Of Different Organo-sulfur Compoundsmentioning
confidence: 99%
See 1 more Smart Citation